The forgotten Creole dish Saint Peter and Saint Paul in the Traditions of Ricardo Palma - Coloma Porcari, César (2019)
This is a research work concerning the history of Peruvian cuisine, broadening theinformation included in La culinaria peruana en las Tradiciones de Ricardo Palma, written by the author and published in Aula Palma (vol. VI, Lima, Instituto Ricardo Palma, Ricardo Palma University, 2008, pp. 169-214). This  essay offers information on the Creole dish called San Pedro y San Pablo (beans with rice), which is mentioned by Ricardo Palma in his Peruvian Traditions and whose name has been completely forgotten. The author reproduces old recipes and the dish is compared with traditional dishes from the Caribbean and Spain that bear some resemblance. Information about the bean (Phaseolus vulgaris L.) and rice (Oryza sativa L.) is included.